Consumer Behavior Assolo’ Pada Acara Pernikahan Suku Kajang Dalam Pesektif Maslahah - Ista, Akram; Muchlis, Saiful; Wahab, Abd. (CV. Lenggogeni Data Publishing, 2024)
The purpose of this research is to describe, explain about consumer behavior assolo’ the wedding event in Suku Kajang in perspective maslahah. This research is qualitative research, the type of research is field research and using an ethnographic approach method. The data collection methods used were observation and interviews. The research results show that consumer behavior assolo' the wedding event in the Kajang Tribe in perspective maslahah namely: 1) pregnant maslahah in the form of maintaining honor and self-respect/say',2) pregnant Maslahah in the form of taawwun values ​​and the embodiment of friendship, and 3) containsThe Value of Maslahah as a Means of Transaction, Distribution of Wealth and Welfare of Property Ownership.So starting from the description above, it can be understood that consumer behavior assolo' the wedding event in the Kajang Tribe in perspective maslahah directly maintain the objectives of Sharia'. Because considering the benefit dimension, besides that assolo' People hold wedding ceremonies to make it easier for them to live their lives, and to keep them away from the negative stigma of society's views.